2019
DOI: 10.1016/j.mehy.2019.109407
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the efficacy of 5-HT uptake inhibitors in the treatment of attention deficit hyperactivity disorder

Abstract: Attention Deficit Hyperactivity Disorder (ADHD) is one of the most common childhood behavioural disorders, the frontline treatments for which are drugs with abuse potential. As a consequence, there is an urgent need to develop non addictive drug treatments with equivalent efficacy. Preclinical evidence suggests that selective serotonin uptake inhibitors (SSRIs) are likely to be effective in ADHD, however clinical reports suggest that SSRIs are of limited therapeutic value for the treatment of ADHD. We propose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 78 publications
(98 reference statements)
0
5
0
1
Order By: Relevance
“…A collection of evidence has revealed that ADHD is associated with monoamine neurotransmitters, like serotonin (5-HT), dopamine (DA), and noradrenaline (NE) ( Mogavero et al, 2018 ). 5-HT system plays a vital role in ADHD from genetics, biochemistry, nerve pathology, and psychological perspectives ( Riley and Overton, 2019 ). Furthermore, the prefrontal cortex (PFC) serves as the chief executive officer of the brain, controlling the highest level of cognitive and emotional processes, which are commonly disrupted in mental illnesses, such as ADHD ( Hiser and Koenigs, 2018 ; Yan and Rein, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…A collection of evidence has revealed that ADHD is associated with monoamine neurotransmitters, like serotonin (5-HT), dopamine (DA), and noradrenaline (NE) ( Mogavero et al, 2018 ). 5-HT system plays a vital role in ADHD from genetics, biochemistry, nerve pathology, and psychological perspectives ( Riley and Overton, 2019 ). Furthermore, the prefrontal cortex (PFC) serves as the chief executive officer of the brain, controlling the highest level of cognitive and emotional processes, which are commonly disrupted in mental illnesses, such as ADHD ( Hiser and Koenigs, 2018 ; Yan and Rein, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been well established that reduced levels of NE and DA in the brain are associated with ADHD. Of late, it has also been shown that a reduced 5-HT level in the prefrontal cortex is a characteristic of ADHD-like impulsive and hyperactive behavior which could be reversed with selective 5-HT reuptake inhibitors [39]. Though it is understood that 5-HT plays a major modulatory role in prefrontal cortex function, it is not clear which 5-HT receptors exert these effects.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic treatment with 5-HT1A receptor agonists (for example, buspirone) has been known to cause antidepressant and anxiolytic effects in both animal and human studies. In contrast to this, Riley and Overton [39] suggest utilizing 5-HT1A antagonists as a potential way forward in the development of pharmacotherapies for ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…Although the role of these neurotransmitters in the pathogenesis of DD is not well established, evidence suggests that treatment with norepinephrine agonists can either exacerbate or improve DD symptoms 11 16 17. Moreover, the patient’s underlying ADHD, which involves complex interactions among dopamine, norepinephrine and serotonin,18 may increase susceptibility to unexpected serotonergic effects of tramadol. However, further investigation is needed to substantiate these speculations.…”
Section: Discussionmentioning
confidence: 99%